Computational study of aerodynamic flow over NACA 4412 airfoil (2017)
The lift and drag coefficient plots for any airfoil provides a means for measuring its aerodynamic characteristics. These are very useful in deciding if a particular airfoil is appropriate for any particular application area. This study computationally predicts how the lift coefficient, drag coefficient and drag polar derived for the aerodynamic flow over the NACA 4412 airfoil vary with angles of attack. The effect of varying Reynolds number on the aerodynamic characteristics was also investigated. The finite-volume based computational fluid dynamics code; ANSYS Fluent was used to solve the continuity equation, the Reynolds Averaged Navier-Stokes equation and the turbulence transport equations governing the flow. For the range of Reynolds number considered, flow was taken as incompressible, steady and two-dimensional. Simulations were run for angles of attack ranging from -10° to 18° with an interval of 2° and for a Reynolds number range of 1.0 x 10(6) to 13.0 x 10(6). Results at a given Reynolds number revealed a steady variation between lift coefficient and angle of attack within the pre-stall region and a gradually increasing curve for the drag coefficients. A constant stalling angle at 14° w ith gradually increasing value for the maximum lift coefficient was recorded as the Reynolds number increased. The drag polar was also found to be constant at 6° for all the ranges of R eynolds number. The results obtained showed that numerically solving for flow problems is a valid approach for obtaining the aerodynamic characteristics of an airfoil since the results were compared with data from wind tunnel tests.